360-degree Strategy for TV Broadcasters in New Media Era: TRT Case Research - Ömer Kısaoğlu (Yeni Medya, 2023)
Television broadcasting develops new forms of distribution with the technological developments. With the inclusion of online opportunities in distribution, new strategies gain importance and current broadcasting activities require a 360-degree strategy. Broadcasters continue to operate on multiple platforms and adopt a 360-degree strategy in order to adapt to changing conditions. This study aims to reveal the activities and broadcasting strategies of the Turkish public service broadcaster TRT in the changing conditions of the sector. The importance of the study is to determine the impact of technological developments on the broadcasting industry. The literature review section analyses the 360-degree strategy and transformation of public service broadcasters with online distribution. Based on the previous studies in the literature, the public service broadcaster TRT from Turkey was taken as a sample. The case research method was used to study the TRT sample. Categories of broadcast distribution formats were created within the framework of the defined 360-degree strategy, and TRT's broadcasting activities were examined under these categories. The most general result obtained as a result of the research is that TRT broadcasts in a wide distribution network and uses on-demand services at a high rate.